PLB’S TEACHERS PEDAGOGICAL COMPETENCE ANALYSIS BASED ON PARTICIPATION INTENSITY IN EDUCATION TRAINING - Martika, Tias (Universitas Pendidikan Ganesha, 2019)
This study aims to map the competencies of teachers in inclusive schools based on the participation of teachers in attending inclusive education training. The subjects of this study were classroom teachers in inclusive schools. Around 38 teachers were selected as samples through purposive random sampling technique. Data were collected using a competency measurement instrument with a reliability value of 0.91. The results obtained were then analyzed using ANOVA one way. Descriptive statistical results show that from the respondents, the mean value of 61.50 was obtained where the lowest value (minimum) was 40 and the highest value (maximum) was 88. Based on One Way ANOVA results, teacher competency scores indicated P (P-value) = 0,000 where P-Value 0,000 <0.05 and F-Value> FTable 24.993> 3.27. This means that there is significant difference in teachers' pedagogical competence based on the involvement in the inclusion training. The findings also showed that 61% of 38 respondents felt it was very necessary to hold training on inclusive education, while 37% said it was necessary enough and 3% said it was not necessary. The materials needed for inclusive education teachers, are in the themes of the understanding of children with special needs, types of children with special needs, the characteristics of children with special needs, how to do identification of special needs, curriculum adaptation for special needs, Individual Learning Program (ILP), learning strategies for special needs, evaluation of learning, the Regulation on education, understanding of full inclusion and segregation, and the inclusive teachers? role on supervising the students? assignments.